CURRENT APPROACHES TO THE STUDY OF EMOTIONAL BURNOUT IN THE CONTEXT OF ITS MANIFESTATION IN REPRESENTATIVES OF VARIOUS PROFESSIONAL GROUPS (LITERATURE REVIEW) - Влах, Надежда Ивановна; Стоянова, Ирина Яковлевна; Данилов, Игорь Петрович; Пестерева, Дина Викторовна (Medicine in Kuzbass, 2025)
At present, in the conditions of high technical requirements and an ever-increasing flow of information, informatization and intensity of work, competition and the need to build interpersonal relationships in the workplace, the problem of professional emotional burnout remains relevant. Psychological manifestations of emotional burnout include emotional exhaustion, excessive anxiety, and personality disintegration. These disorders are most often observed in workers in the service sector or medicine in response to a constantly high intensity of social contacts, which ultimately leads to the risks of psychological and physiological disorders.For this reason, emotional burnout has been studied mainly among workers in «helping» professions: teachers, doctors, medical and social workers, and psychologists. The study of this phenomenon among workers in other fields of professional activity is extremely insufficient, especially among workers in industrial and resource-producing industries. For example, it seems significant to study the emotional burnout of workers in the main professions of the coal industry – the leading one in Kuzbass, that occupies a leading position in the country in terms of the number of people working in harmful and (or) hazardous working conditions – 374.6 thousand people, 13% of whom are engaged in mining and petroleum production. The share of workers with harmful and (or) hazardous working conditions from the total number of employed workers in the main types of economic activity in the region is 67.5%.The search and selection of sources to identify the main directions of studying the features of emotional burnout in representatives of various professions, including workers in the coal mining industry, were carried out using bibliographic databases, such as Scopus, MedLine, Web of Science, PubMed, The Cochrane Library, RISC, CyberLeninka. The research results presented in the review by domestic and foreign authors indicate a variety of approaches to the study of this phenomenon. Scientists agree on the need to identify early signs of emotional burnout, monitor psycho-emotional state, and determine the risk groups among workers of various professional cohorts for timely prevention and correction. Data analysis showed that there are relatively few studies on the psychological health of workers engaged in harmful and/or hazardous working conditions, including miners; they mainly concern clinical issues and require immediate, close study.
Keywords: emotional burnout; professional burnout; «helping» professions; workers of coal mining industry; review